THE INFLUENCE OF PRODUCTION COSTS, PROMOTION AND SALES COSTS ON COMPANY PROFITS (Empirical Study of Manufacturing Companies in the Food and Beverage Sector Registered at BEI Period 2018-2021) - Utami, Wikan Budi; Zahrah, Aini; Kristiyanti, LMS (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Net profit is the limited measure of a company's success. The main purpose of establishing a business or company is to make a profit. Planning and controlling profits is one of the roles of company management that is really needed, to generate maximum profits. The following are the factors that influence making a profit, namely production costs, promotion costs, and sales. This research aims to determine the influence of production costs, promotion and sales costs on company profits. In this research, the sample used is food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The analysis method uses multiple linear regression analysis methods with a significance level of 5% or 0.05. The research results show that the production cost variable with a significance value of 0.000 < 0.05, the promotion cost variable with a significant value of 0.003 < 0.05 and the sales variable 0.000 < 0.05 affect the profits of manufacturing companies listed on the Indonesia Stock Exchange, this can be seen from the results of the t-test. The results of the f- test show that production costs, promotion costs and sales have a joint effect on company profits, the R2 value is 79,3%. Keywords: Production Costs, Promotion Costs, Sales, Profit